Integrative review of remote patient monitoring in gynecologic and urologic surgical oncology. Issue 6 (23rd February 2023) - Perez, Fernanda; Nolde, Margaret; Crane, Tracy E.; Kebria, Mehdi; Chan, Kevin; Dellinger, Thanh; Sun, Virginia
Abstract: Patients with cancer facing complex and invasive urologic and gynecologic cancer surgery often experience symptoms and rapid declines in functional capacity postoperatively. Remote patient monitoring that leverages patient‐generated health data is a potential approach to assess and promote postoperative recovery. This integrative review aims to provide an overview of the current literature and research on remote patient monitoring in gynecologic and urologic surgical oncology.